Physiological Characterization and Molecular Identification of Denitrifying Bacteria Possesing Nitrous Oxide High Reduction Activity Isolated from Rice Soils - RATNA SETYANINGSIH; IMAN RUSMANA; PRIHASTO SETYANTO; ANTONIUS SUWANTO (Indonesian Society for microbiology, 2010)
Rice fields are one of the main sources of high nitrous oxide N2O emission. Soil denitrifiers possessing high N2O reduction activity are important for controlling N2O emission. Nitrous oxide reduction is the last step of denitrification process. The aims of this study were to characterize and to identify denitrifying bacteria isolated from rice soils possessing high activity of N2O reduction. Soil samples were taken from 6 locations of rice fields in Bogor (West Java) and Tangerang (Banten), Indonesia. Physiological characterization was performed using API 20 NE, while molecular identification was conducted based on the 16S rRNA gene sequence. It was found that ten isolates of denitrifying bacteria were able to grow using N2O as an electron acceptor as indicated by decreasing N2O concentration in the headspace of the cultures. The bacterial growth indicated by optical density, increased up to 0.12-0.47 after 5 days incubation. Isolate BL2 had the highest activity of N2O reduction followed by BL1 and BLN1 at up to 5.41, 4.09, and 3.91 μmol mL-1 bacterial cultures, respectively. The BL1, BL2, and BLN1 isolates had some different physiological characteristics. Based on their 16S rRNA sequence, BL1 and BLN1 were closely related to Ochrobactrum anthropi ATCC 49188 with similarity of 99%.